Research results of the krill catching trawler “Cooperation Sea” in the Antarctic krill fishing area of the Atlantic Antarctic and its biological state during the winter 2014 - N. N. Zhuk; Yu. V. Korzun (Ukrainian Antarctic Journal, 2014)
Results of the data analysis on the Antarctic krill Euphausia superba biology, fisheries, and hydrometeorological conditions, collected by the National observer on board the Ukrainian krill catching trawler “Cooperation Sea” are presented. The vessel conducted krill fishery activities in the Atlantic Antarctic (AA), CCAMLR zone (subareas 48.1, 48.2, 48.3) during the winter season (April-July) of 2014. The defined sizes of the krill in the catches made up 24-59 mm. Small- and medium-sized krill of 26-47 mm length and aged 1+, 2+, 3+, 4+ at the early stages of sexual maturity dominated in the catching areas. The feeding intensity of krill was weak or moderate. The amount of molting crustaceans and those, infected by the bacteria of the genera Psychrobacter and Pseudoalteromonas, was not significant: 4-6% and 0.07-6%, correspondingly. The infected crustaceans were observed in all the subareas, the tendency of the crustaceans infection increase was marked in the direction from the south northwards. Prevalence of the recruits and medium-sized specimens in the euphausiids group catches allows to predict high krill abundance in the AA during the next fishing season of 2014-2015. Weather conditions in all the fishing areas were mostly determined by the winds of western and northern directions, except for the area of the South Shetland Islands, where meteorological conditions in May were characterized by eastern winds, wind speed increase, decrease of average means of air and surface temperatures, divergent changes of atmospheric pressure, preconditions to ice formation and solid ice cover (except for area 48.3). The total krill catch during the cruise made up 8,900 tons; average means of CPUE and catch per fishing day reached 8,400 tons and 114,500 tons, correspondingly. In order to rationally use krill resources, it is suggested to reconsider the distribution of its catch threshold according to the fishing subareas, established by CCAMLR, in favor of increasing the krill catch limit in the area of the South Shetland Islands.